Successes and challenges of artificial intelligence in cardiology - Vandenberk, Bert; Chew, Derek S.; Prasana, Dinesh; Gupta, Sunny; Exner, Derek V. (Frontiers in Digital Health, 2023)
In the past decades there has been a substantial evolution in data management and data processing techniques. New data architectures made analysis of big data feasible, healthcare is orienting towards personalized medicine with digital health initiatives, and artificial intelligence (AI) is becoming of increasing importance. Despite being a trendy research topic, only very few applications reach the stage where they are implemented in clinical practice. This review provides an overview of current methodologies and identifies clinical and organizational challenges for AI in healthcare.